(1x+8)-14=-15

Simple and best practice solution for (1x+8)-14=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1x+8)-14=-15 equation:


Simplifying
(1x + 8) + -14 = -15

Reorder the terms:
(8 + 1x) + -14 = -15

Remove parenthesis around (8 + 1x)
8 + 1x + -14 = -15

Reorder the terms:
8 + -14 + 1x = -15

Combine like terms: 8 + -14 = -6
-6 + 1x = -15

Solving
-6 + 1x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 1x = -15 + 6

Combine like terms: -6 + 6 = 0
0 + 1x = -15 + 6
1x = -15 + 6

Combine like terms: -15 + 6 = -9
1x = -9

Divide each side by '1'.
x = -9

Simplifying
x = -9

See similar equations:

| 17+3n=21+2n | | 5t-15-2t=-30 | | 14-2x+16-3a-7=-11 | | (x-28)+(2x-16)(0.5x+14)=180 | | 7n-31=11 | | 5/x=2.4 | | 11x-6=2(5x+4)-2 | | 8x+6x-9x=-2-x-15 | | 6+2m-5=6m+19-2m | | 1x-6=-14 | | 25=3+4+2x+5x | | 6n-13=5n+16 | | f(x)=x^2-4x+17 | | 7z+3/7=8z+1/7 | | 2+X=-10+8 | | 40y^2-39x-40= | | 1.3/10-3.2/5= | | 1=-1(-1w+6) | | 256^1/2=32^-2x-4/5 | | 2/3(6x+3)=8x+2-4x | | 0.25=0.25x+4 | | (5/2X)+(2/3X)=(95/2X) | | 18x^2+39x-7=(6x-1) | | -2(-8x+6)=10x+2(1+10x) | | 9-3x=7x-2(5-x) | | 1/3(3+9x)=7/4(28-12x) | | 2(10m-7a)+3(8a-3m)=0 | | x-7=-5.5 | | 360=35+35+x | | 5d+4=3(2-d)+8d | | 18+6g=4g | | 31+4t-t= |

Equations solver categories